Real-time in vivo assessment of radiofrequency ablation of human colorectal liver metastases using diffuse reflectance spectroscopy. Issue 2 (February 2016) - Tanis, E.; Spliethoff, J.W.; Evers, D.J.; Langhout, G.C.; Snaebjornsson, P.; Prevoo, W.; Hendriks, B.H.W.; Ruers, T.J.M.
Abstract: Background: The success of radiofrequency (RF) ablation is limited by the inability to assess thermal tissue damage achieved during or immediately after the procedure. The goal of this proof-of-principle study was to investigate whether diffuse reflectance (DR) spectroscopy during and after RF ablation of liver tumours could aid in detecting complete tissue ablation. Material and methods: DR spectra were acquired in vivo in eight patients undergoing RF ablation for unresectable colorectal liver metastases, using a disposable spectroscopy needle. Intraoperative ultrasound imaging was used for accurate positioning of the RF electrode and the spectroscopy needle. Spectral changes were quantified and correlated to tissue histopathology and follow-up CT imaging. Results: For the lesions in which ablation was monitored by DR spectroscopy (N = 8), median tumour size was 1.6 cm (range 0.8–3.3 cm). We found an excellent correlation (97–99%) between thermal damage suggested by spectral changes and histology. DR spectroscopy allowed discrimination between non-ablated and ablated tissue, regardless whether the needle was placed in tumour tissue or in surrounding liver tissue. Additional measurements performed continuously during ablation confirmed that the magnitude of spectral change correlates with the histochemical degree of thermal damage. Conclusions: Diffuse reflectance spectroscopy allows accurate quantification of thermal tissue damage during and after RF ablation. Real-time feedback by DR spectroscopy could improve the accuracy and quality of the RF procedures by lowering incomplete ablation rates.